2020
DOI: 10.1186/s13256-020-02490-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine appendiceal tumor and endometriosis of the appendix: a case report

Abstract: Introduction Endometriosis of the appendix is very uncommon, accounting for only about 1% of all cases of endometriosis. However, endometriosis is found in the appendix in approximately 8–13% of patients with deep infiltrating endometriosis and is particularly common in patients with severe forms of deep infiltrating endometriosis. Neuroendocrine tumors are the most common neoplasms of the appendix and may be misdiagnosed when there are multiple endometriosis lesions in the pelvis. Case presentation We descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…The analysis of the appendix of one patient revealed a well-differentiated neuroendocrine carcinoma at the appendix tip. 14 The ileum was involved in 6% of cases. Only 2 patients (1.3%) did not have rectosigmoid involvement and underwent laparoscopy: one due to isolated small bowel (ileal) involvement and the other due to ileal and appendix involvement.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the appendix of one patient revealed a well-differentiated neuroendocrine carcinoma at the appendix tip. 14 The ileum was involved in 6% of cases. Only 2 patients (1.3%) did not have rectosigmoid involvement and underwent laparoscopy: one due to isolated small bowel (ileal) involvement and the other due to ileal and appendix involvement.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the etiology of neuroendocrine carcinoma of the appendix remains unclear. Recent reports have indicated that endometriosis may be related to the occurrence of neuroendocrine carcinoma of the appendix [ 24 , 25 ]. Virgine C et al described five children with neuroendocrine tumors of the appendix (NET) associated with parasitic intestinal infections and discussed the possibility of inflammation leading to canceration.…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis implants have been identified on the appendix during a histopathologic review, and studies have suggested that the appendix may contribute to chronic pelvic pain [ 4 , 5 ]. Coexisting endometriosis and appendiceal neuroendocrine tumors have also been identified during gynecologic surgeries [ 6 , 7 ]. One systematic review identified that the rates of ANETs are the same in endometriosis patients as in the general population, which suggests that endometriosis is not a risk factor for ANETs [ 8 ].…”
Section: Discussionmentioning
confidence: 99%